2016
DOI: 10.1002/acp.3226
|View full text |Cite
|
Sign up to set email alerts
|

Structure Building Predicts Grades in College Psychology and Biology

Abstract: Knowing what skills underlie college success can allow students, teachers, and universities to identify and to help at-risk students. One skill that may underlie success across a variety of subject areas is structure building, the ability to create mental representations of narratives (Gernsbacher, Varner, & Faust, 1990). We tested if individual differences in structure-building ability predicted success in two college classes: introductory to psychology and introductory biology. In both cases, structure build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In our sample of college students, beta Coach predicts as much variance in final exam performance as the text MMCB (15%). These results are similar to those of Arnold et al (), who demonstrated that the MMCB significantly predicted final course grades in introductory biology and psychology courses. Our results also complement the previous work by Maki and Maki () who found that the MMCB predicted performance on an average of four course examinations in introductory psychology courses after controlling for prior knowledge and instructor variance.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our sample of college students, beta Coach predicts as much variance in final exam performance as the text MMCB (15%). These results are similar to those of Arnold et al (), who demonstrated that the MMCB significantly predicted final course grades in introductory biology and psychology courses. Our results also complement the previous work by Maki and Maki () who found that the MMCB predicted performance on an average of four course examinations in introductory psychology courses after controlling for prior knowledge and instructor variance.…”
Section: Discussionsupporting
confidence: 90%
“…In two prior studies, structure building ability predicted final course grades (Arnold et al, ) and average exam performance (Maki & Maki, ). To add to this existing literature, we examined whether structure building ability would predict comprehensive final exam scores.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…MMCB. Students' general structure building ability of text was measured using the written version of the MMCB (also see Arnold et al, 2016;Bui & McDaniel, 2015;Callender & McDaniel, 2007;Martin et al, 2016 for studies using the written version of the MMCB). We chose the MMCB because it is a measure of general comprehension skill of written materials.…”
Section: Methodsmentioning
confidence: 99%